Improving EFL Students’ Higher Order Thinking Skills Through Collaborative Strategic Reading in Indonesia - Arik Susanti; Pratiwi Retnaningdyah; Ade Nila Puspita Ayu; Anis Trisusana (International Journal of Asian Education, 2020)
The study aims to investigate whether collaborative strategic reading (CSR) strategies can improve higher-order thinking skills (HOTS) of students. It is an experimental design using pre-test and post-test as an instrument. Research data was obtained by giving a reading test in one of the public vocational high schools in Surabaya, Indonesia. These test data were analyzed using independent sample T-test and paired sample T-test in SPSS. Results showed that Collaborative Strategic Reading (CSR) could improve higher-order thinking skills for students. Based on data analysis results, t count was found to be larger than t table. Moreover, the result of the paired-sample t-test also indicated a significant difference between pre-test and post-test scores of experimental students. Sig. Sig. (2-tailed) equals.000. To sum up, the strategy benefits students in enhancing higher-order thinking skills for students.